Introduction of enhanced compressive residual stress profiles in aerospace components using combined mechanical surface treatments - Gopinath, Abhay (2018)
Mechanical surface treatments such as Shot Peening (SP) and Deep Cold Rolling (DCR) are being used to introduce Compressive Residual Stress (CRS) at the surface and subsurface layers of aerospace components, respectively. This paper investigates the feasibility of a combined introduction of both the surface and sub-surface compressive residual stress on Ti6Al4V material through a successive application of the two aforementioned processes, one after the other. CRS profiles between individual processes were compared to that of combination of processes to validate the feasibility. It was found out that shot peening introduces surface compressive residual stress into the already deep cold rolled sample, resulting in both surface and sub-surface compressive residual stresses in the material. However the drawback of such a combination would be the increased surface roughness after shot peening a deep cold rolled sample which can be critical especially in compressor components. Hence, a new technology, Vibro-Peening (VP) may be used as an alternative to SP to introduce surface stress at reduced roughness.